A minimally invasive fixation for boxers fracture – fifth metacarpal neck using antegrade K wire fixation – functional outcome study - Pamarthi Srinivas; Sai Phanindra M (Asian Journal of Medical Sciences, 2024)
Background: Fifth metacarpal fractures are more common fractures in hand which are treated by conservative or surgical methods. Using retrograde k-wire fixation is associated with more complications due to damage to articular surface causing deformity or decreasing range of motion. Studies are done using single k-wire usage by antegrade technique, results vary due to k-wire complications and surgeon experience. Aims and Objectives: In this study, we are used a technique to bend a K wire in S-shaped fashion to negotiate through fracture to hold and reduce the fracture by rotating the tip of K-wire. Materials and Methods: This prospective study was done for fracture neck of fifth metacarpal presenting to outpatient department in 36 patients with dorsal angulation of more than 300 treated by passing a single k wire bent at the tip and shaft to form an S shape retrogradely with a follow-up period of 6 months following surgery. Results: Majority of injuries were in males in the dominant hand with a mean age group of 27.25 years. The mean pre-operative flexion angle of distal fragment was 44.11° (SD–4.12), and after the end of follow-up healing was achieved in all cases with a mean flexion angle improvement to 5.25° (SD–2.16). Disabilities of the arm, shoulder, and hand score measured at the end of study showed a mean of 6.25, and total active motions core showed excellent results in 25 cases (69.4%) cases and poor in 1 case (2.77%). Conclusion: This study emphasizes that bending a K wire in a lazy S fashion and passing antegradely will replicate results similar to using 2 K wires and have a better prognosis than retrograde wiring through the head of metacarpal. Furthermore, this procedure can be done in a primary care setting with minimal resources.